Effect of wind speed and angle of attack on aerodynamic characteristics of naca0012 airfoil - Taresh Dawood, basima (University of Thi-Qar Journal, 2024)
The study of the aerodynamic properties of wings is considered one of the most prominent topics in the field of aircraft manufacturing in general and drones in particular. This research focuses on studying the aerodynamic properties of an unmanned aerial vehicle wing with a streamlined aerodynamic section that falls under the NACA 0012 classification. The wing is made of aluminium, with dimensions of 30 x 30 cm. It was tested at angles of attack (0, 5, 10, 15, 18 degrees) and at speed values of 12, 15, 18, 21, and 23 metres per second to determine the aerodynamic features of the test section. This test was done through a subsonic tunnel. These parameters are crucial in understanding how a wing behaves under different flight conditions. One of the most prominent results reached in this research is the increase in drag forces when the angle of attack and wind speed increase. The maximum value obtained is 9.6 Newtons at an angle of attack of 18 degrees and a wind speed of 23 m/s. The maximum lift factor was 0.1856 at an angle of attack of 15 degrees and an average wind speed of 21 m/s.